ANALISA KERUSAKAN PIPA DUCTING SCRUBBING BERBAHAN CARBON STEEL SS400 DI PABRIK PUPUK NPK-1 PT PUSRI PALEMBANG - Nasrah, Perez; Homzah, Ozkar F. (Politeknik Negeri Sriwijaya, Indonesia, 2023)
The purpose of this research was to discover the various reasons of failures and appropriate repair options for the line ducting cleaning unit system at PT Pusri Palembang's NPK-1 production facility. The main cause of the failures was determined to be a deterioration of the ducting line material caused by corrosion on the inner side of the ducting pipe composed of SS400 carbon steel. We made investigation including an analysis of the thickness of the damaged ducting pipe, as well as a visual check. The investigation showed that the corrosion caused an average drop in pipe wall thickness of up to 70%. The fixed load superimposed on the ducting pipe and the carrying capacity of the piping affect ducting strength, but corrosion on the inner surface of the pipe, caused by direct contact with corrosive and hygroscopic process dust, reduces ducting wall strength against axial and lateral loads. A Failure pipe caused losses and unscheduled shutdowns of production process, will be increased the repair costs and increases the risk of human accidents. The suggestion of investigation results is to upgrade the ducting pipe materials to knowed corrosion-resistant materials, such as stainless-steel grade SS304. Also, should be taken is also regularly to inspect the ducting cleanness for the internal of ducting and control the dust flow rate through the scrubbing system. As conclusion, the suggestions given are to mitigate the risk of corrosion impact by maintaining ducting strength within the minimizing ducting system failures and ensuring the NPK plant's operation reliability.